Technique of reintervention for stent dysfunction in patients with malignant hilar biliary stricture. (25th April 2013) - Okabe, Yoshinobu; Ishida, Yusuke; Ushijima, Tomoyuki; Sugiyama, Gen; Sata, Michio
Abstract : At present, the endoscopic approach is the most commonly adopted method for stenting in patients with unresectable malignant hilar biliary stricture. This procedure is important, as it determines the quality of life and prognosis of the patient. Regarding the quality of the stent material, self‐expandable metallic stents (SEMS) are expected to show longer‐term stent patency than plastic stents (PS), and their use as devices of first choice has been increasing. However, complications such as stent occlusion due to tumor ingrowth or biliary sludge formation occur at a considerably high frequency, necessitating reintervention in a considerable number of patients. In the case of dysfunction of an implanted PS, the stent is removed, and the lumen ofthe bile duct is cleaned, followed by placement of a new stent. In the event of dysfunction of a SEMS, cleaning of the lumen of the SEMS and placement of a second stent (PS is preferable) are carried out. Nevertheless, the results have not been entirely gratifying. Development of SEMS or PS suited to multidisciplinary treatment that would enable uncomplicated reintervention is anticipated.